The effect of quercetin on the pharmacokinetics of chlorzoxazone, a CYP2E1 substrate, in healthy subjects - Bedada, Satish Kumar; Neerati, Prasad (European journal of clinical pharmacology, 2018)
Purpose Previous in vitro studies have demonstrated that quercetin inhibits CYP2E1 enzyme, but there are no available data to indicate that quercetin inhibits CYP2E1 enzyme in humans. The purpose of the present study was to assess the effect of quercetin on CYP2E1 enzyme activity in healthy subjects using chlorzoxazone (CHZ) as a CYP2E1 substrate. Methods An open-label, two-period, sequential study was conducted in 12 healthy subjects. A single dose of CHZ 250 mg was given to subjects during control phase and after treatment phases. Quercetin at a dose of 500 mg was given to subjects twice daily for a period of 10 days. The blood samples were collected at predetermined time intervals after CHZ dosing and analyzed to determine the concentrations of CHZ and 6-hydroxychlorzoxazone (6-OHCHZ). Results Treatment with quercetin significantly enhanced the maximum plasma concentration ( C max ), area under the curve (AUC), and half-life ( t 1/2 ) by 47.8, 69.3, and 36.4%, respectively, while significantly decreased the elimination rate constant ( k el ) and apparent oral clearance (CL/F) of CHZ by 25.1 and 41.6%, respectively, in comparison with the control. On the other hand, C max and AUC of 6-OHCHZ were decreased by 30.1 and 32.6%, respectively, after quercetin treatment when compared to control. In addition, geometric mean ratios and 90% confidence intervals for C max and AUC of CHZ and 6-OHCHZ were both out of the no-effect boundaries of 0.80–1.25, which indicates a significant pharmacokinetic interaction present between CHZ and quercetin. Furthermore, treatment with quercetin significantly decreased the metabolic ratios of C max and AUC by 57.1 and 60.1%, respectively, as compared to control suggesting that reduced formation of CHZ to 6-OHCHZ. Conclusions The results suggest that altered pharmacokinetics of CHZ might be attributed to quercetin-mediated inhibition of CYP2E1 enzyme. Further, the inhibition of CYP2E1 by quercetin may represent a novel therapeutic approach for minimizing the ethanol-induced CYP2E1 enzyme activity and results in reduced hepatotoxicity of ethanol.